I wonder why spiders spin webs : and other questions about creepy-crawlies - O'Neill, Amanda (I wonder why (New York, N.Y.), 2011)
Answers questions about insects and spiders, including, "Which insect listens with its legs?" and "Why do glowworms glow?"